Harmonisation of social policy in the European Community - Bieback, Karl-Jürgen (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1991)
With the completion of the Common Market by the end of 1992 the issue of harmonisation of EC law and the Member States is being intensively discussed. Most articles concentrate on discussing the direct effects that EC law has on the law of the Member States. However, in the field of social policy EC competences are very limited as this is still within the prerogative power of the Member States. This paper analyses the problem that the regulatory power and weight of the EC are much greater than its direct competences and regulations mainly through the legal, economic and social influences a common market will exert on the legal order of the Member States. One point is the "natural" tendency of (con-)federated political systems to extend the existing limited competences of the centre. This is not only a matter of "implied powers" granted to the larger political unit, but also of the predominance of EC competence to establish a free market over the Member States' competence to regulate their social policy. The second point is the various influences the free market of the Community will have on the structure of the respective social policies of the Member States : social dumping ; limits to national regulations of social services which disturb the free market for services and goods ; the mobility of labour and the exports of social benefits. Although most mechanisms of harmonisation are illustrated by examples of German labour and social security law, the problems apply to all other Member States of the EC and even to a country, like Canada, which is part of a larger zone of free trade and which itself forms a federal system with a fragile balance between the competences of the Federation and the Member States.